EFFECTS OF PROJECT LIFE CYCLE MANAGEMENT ON PERFORMANCE OF WATER DEVELOPMENT PROJECTS IN KENYA (A CASE OF KITUI COUNTY) - NYAMASEGE, EMILY BISIERI; MBURU, DAVID KIARIE (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
The Kenyan government and international organizations have continued to invest in the implementation of water development projects to assist the rural communities to alleviate the problem of water scarcity. The performance of these projects is the major problem as they are not successful and falling out of use at an alarming rate. In order to make the investment in implementation of water development projects more effective and worth, success rates of these projects should be increased. The study therefore examined the effect of project life cycle management on the performance of water projects in Kenya as the main objective of the study. The study adopted a descriptive research approach which involved using case study design. A stratified random sampling design was used whereby 37 respondents formed 10% of the target population. A pilot study was conducted to pretest the validity and reliability of instruments for data collection. The study involved the use of questionnaire method to collect data. The data was analyzed by use of both qualitative and quantitative methods with the help of Statistical Package for Social Sciences (SPSS) version 21 and excel. The study findings showed that project initiation phase, project planning phase, project execution phase and project closure phase had effects on the performance of the water development projects in Kenya. The correlation and regression analysis showed they had positive relationship and this implies that they influenced performance of water development projects with a significant relationship at 5% level of significance and 95% level of confidence. The study established that project planning phase was the most significant factor. Based on these findings, the study recommends that an evaluation to be conducted on the implemented projects to establish whether the project life cycle management was considered and what led to project delays in implementation thus affecting the performance of such projects in other areas of Kenya for the generalization of the findings of the study